Incidence of Binge Drinking in a Cohort of University Students of the South-East Region of Brazil, 2010-2011 - Guimarães, Nathalia Sernizon; Nemer, Aline Silva de Aguiar; Lima, Claúdia Aparecida Marliére; Costa, Juliana Inácio; Fausto, Maria Arlene (Journal of Nutritional Therapeutics, 2013)
Objectives: The aim of the present study was to evaluate the prevalence and incidence of binge and at-risk alcohol consumption among new-entrant students in a public university in the South-East Region of Brazil. Methods: Longitudinal study undertaken with a random sample of undergraduates (N=1,168) in the first semesters of 2010 (n=256) and 2011 (n=183). In order to evaluate drinking patterns, participants were classified as abstainers, light, moderate, binge or heavy binge drinkers. The Alcohol Use Disorders Identification Test (AUDIT) questionnaire score was used to define the risk categories for consumption: low risk, risk, harmful use and probable dependence. Statistical analysis was undertaken using Stata software, version 11.0. Results: Amongst the 256 students evaluated, 51.6% were women and 64.5% were aged ≥19 years. The prevalence of consumption of alcoholic beverages was 75.8%. The average age of onset of alcohol consumption was 15.7±1.9 years. The incidence of binge + heavy drinkers was 2.6/100 persons per year, with vulnerability shown in individuals of male sex and of age 19 years or more. The incidence of risk level drinkers was 2.0/100 persons per year and greater for individuals of male sex and younger than 19 years. Conclusion: The students of this institution are at high risk for problems associated with alcohol use.